2015
DOI: 10.1139/cjfas-2014-0192
|View full text |Cite
|
Sign up to set email alerts
|

Anadromy and residency in steelhead and rainbow trout (Oncorhynchus mykiss): a review of the processes and patterns

Abstract: Abstract:Oncorhynchus mykiss form partially migratory populations with anadromous fish that undergo marine migrations and residents that complete their life cycle in fresh water. Many populations' anadromous components are threatened or endangered, prompting interest in understanding ecological and evolutionary processes underlying anadromy and residency. In this paper, we synthesize information to better understand genetic and environmental influences on O. mykiss life histories, identify critical knowledge g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
224
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(245 citation statements)
references
References 163 publications
(435 reference statements)
3
224
0
Order By: Relevance
“…The phenotypic plasticity of steelhead, including iteroparity and the existence of nonanadromous rainbow trout that are often functionally part of the steelhead population (Courter et al 2013;Kendall et al 2015), and the difficulties associated with accurately counting the fish (e.g., low abundance, protracted arrival timing, and often difficult surveys) can challenge our ability to detect trends in population abundance. For example, declining survival during migration to and from the ocean and in the ocean can lead to an increase in the proportion of resident individuals in O. mykiss populations (Kendall et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotypic plasticity of steelhead, including iteroparity and the existence of nonanadromous rainbow trout that are often functionally part of the steelhead population (Courter et al 2013;Kendall et al 2015), and the difficulties associated with accurately counting the fish (e.g., low abundance, protracted arrival timing, and often difficult surveys) can challenge our ability to detect trends in population abundance. For example, declining survival during migration to and from the ocean and in the ocean can lead to an increase in the proportion of resident individuals in O. mykiss populations (Kendall et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, declining survival during migration to and from the ocean and in the ocean can lead to an increase in the proportion of resident individuals in O. mykiss populations (Kendall et al 2015). Thus, steelhead population abundance declines may not represent a trend towards that population's extirpation but may instead suggest a change in the dominant life history strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant densities as observed in the summer and fall might therefore not reach levels that affect individual growth rates. In an evolutionary perspective, this behavior is a driving factor in the development of anadromy (Gross 1987, Kendall et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…These studies detected three juvenile Rainbow Trout/ steelhead in the mainstem Columbia River (fish that had been initially captured and tagged in Rattlesnake and Buck creeks), indicating an attempt at anadromous migration nearly 100 years after Condit Dam had blocked upstream access. Resident and fluvial Rainbow Trout are known to contribute to anadromous populations (Hayes et al 2012;Weigel et al 2013;Kendall et al 2015) and have been shown to speed population recovery after disturbance (Parker et al 2001). A juvenile fish assessment with a rotary screw trap was conducted by USGS and USFWS for four years, beginning in 2006, to determine species composition and abundance of salmonids in the river downstream of Condit Dam (Allen and Connolly 2011).…”
Section: Working Group Effortsmentioning
confidence: 99%